Development of aminoquinoline-benzimidazole hybrids and their organometallic complexes as antimicrobial agents against Plasmodium falciparum and Mycobacterium tuberculosis - Baartzes, Nadia (Department of Chemistry, 2020)
Malaria and tuberculosis (TB) are infectious microbial diseases contributing to a major global health problem and remain a high priority.The problem is further compounded by the emergence of drug resistant strains of the respective causative agents. New therapies and drug design strategies are thus continually required to overcome this resistance. A unique approach in tackling rising resistance is the use of hybrid chemotherapy, which involves the combination of two or more pharmacophores into a single compound. This study investigated the synthesis, characterisation and pharmacological properties of new organic and ferrocenyl aminoquinoline-benzimidazole hybrid compounds, as well as the corresponding Platinum Group Metal (PGM)-containing complexes. The compounds were screened for their activity against Plasmodium falciparum, and for their cytotoxicity against the Chinese hamster ovarian (CHO) cell-line. In addition, the compounds were also evaluated against Mycobacterium tuberculosis. A series of aminoquinoline-benzimidazole hybrid compounds were prepared. The 2-position of the benzimidazole was substituted with an organic phenyl or pyridyl group, or an organometallic ferrocenyl group. The 5-position of the benzimidazole was varied using substituents with varying hydrophobic and electron-withdrawing or -donating properties, in order to probe the effect on biological activity. These compounds were fully characterised using 1H, 13C{1H}, COSY and HSQC NMR spectroscopy, IR spectroscopy and electrospray ionisation mass spectrometry. The organic and ferrocenyl aminoquinoline-benzimidazole hybrids were screened in vitro against the chloroquine-sensitive (CQS) NF54 strain and multidrug-resistant (MDR) K1 strain of P. falciparum. Most compounds displayed good activity against the sensitive NF54 strain, with IC50 values in the low to sub-micromolar range. With the exception of the pyridyl analogues, most compounds were more potent in the resistant K1 strain. Resistance indices lower than one (RI < 1) were observed in most cases, indicating greater applicability in the resistant strain. The individual aminoquinoline and benzimidazole components were also evaluated in order to determine the value in the use of hybrid agents in comparison to the individual components. In the K1 strain, thehybrid proved more potent than either of the individual components. Using isobologram analysis in the NF54 strain, additive and antagonistic relationships were revealed for the co-administration of the aminoquinoline and benzimidazole components in different relative concentrations. All of the tested hybrids displayed low or no cytotoxicity towards CHO cells and consequent selectivity towards Plasmodium strains. The most active phenyl and ferrocenyl hybrids were subsequently screened for in vivo efficacy against P. bergheiinfected mice. Treatment with the ferrocenyl hybrid resulted in a 92% reduction in parasitemia, proving a more potent inhibitor than the phenyl hybrid (58%). The haem degradation pathway is a known target of many antimalarials, and thus haemozoin inhibition was investigated as a possible mechanism of action of these hybrid compounds. All screened hybrids were found to inhibit synthetic haemozoin (β-haematin) formation in a cell-free assay. A cellular haem fractionation assay was performed on the most active ferrocenyl hybrid, confirming haemozoin inhibition in the parasite. In addition, reactive oxygen species (ROS) generation by this ferrocenyl hybrid was explored using a DNA-cleavage assay, revealing insignificant ROS-generating ability. Furthermore, the aminoquinoline-benzimidazole hybrids were evaluated in vitro against the H37Rv strain of M. tuberculosis. For the phenyl and ferrocenyl hybrids, those with the less hydrophobic 5-position substituents were inactive, while those with the more hydrophobic substituents showed moderate to good activity. Based on logP values, there was a positive correlation between lipophilicity and antimycobacterial activity. In line with this, the more lipophilic ferrocenyl hybrids were consistently more active than their corresponding less lipophilic phenyl analogues. Additionally, in an evaluation of the individual aminoquinoline and benzimidazole components, the hybrid compound was more potent than either component administered individually. The active phenyl hybrid ligands were reacted with [Ir(Cp*)Cl2]2 and [Rh(Cp*)Cl2]2 to yield neutral C^N-coordinated and N-coordinated hybrid complexes. Furthermore, the pyridyl hybrid ligands were reacted with [Ir(Cp*)Cl2]2, [Rh(Cp*)Cl2]2, as well as [Rh(ppy)2Cl]2 to afford cationic N^N-coordinated hybrid complexes. The complexes were fully characterised using the aforementioned spectroscopic and analytical techniques. The C^N- and N^N-coordinated PGM-containing complexes were screened against the NF54 and K1 strains of P. falciparum, generally displaying low to sub-micromolar IC50 values across both strains. In the sensitive NF54 strain, the cationic Rh(III)-ppy complexes were most potent, outperforming the neutral and cationic M-Cp* complexes. The selected complexes (NF54 IC50 ≤ 2 µM) tested in the resistant K1 strain, generally had activity comparable to or lower than that in the NF54 strain (RI ≥ 1). The active hybrid complexes were evaluated against the non-tumorigenic CHO cell-line, displaying low or no cytotoxicity overall. With regards to a possible mechanism of action, the hybrid complexes were found to be potent inhibitors of β-haematin formation. The catalytic ability of selected Ir(III) and Rh(III) C^N-coordinated hybrid complexes, in the transfer hydrogenation of NAD+ to NADH, was also investigated. Using sodium formate as the hydride source, both complexes demonstrated the ability to catalyse the conversion under cell-free assay conditions. However, co-administration of the Ir(III) complex with sodium formate did not have a significant effect on parasite viability. When evaluated against the H37Rv strain of M. tuberculosis, the hybrid complexes generally displayed moderate to good activity. The neutral M-Cp* and cationic Rh(III)-ppy complexes significantly outperformed the cationic M-Cp* complexes. Overall, the neutral Ir(III)-Cp* complexes were most potent, displaying MIC90 values in the low to sub-micromolar range.